2018
DOI: 10.1556/2006.7.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the relation between pathological gambling and depression: Rumination as an underlying common cause

Abstract: Background and aimsSymptoms of pathological gambling (SPG) and depression often co-occur. The nature of this relationship remains unclear. Rumination, which is well known to be associated with depression, might act as a common underlying factor explaining the frequent co-occurrence of both conditions. The aim of this study is to analyze associations between the rumination subfactors brooding and reflection and SPG.MethodsParticipants aged 14–64 years were recruited within an epidemiological study on pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…There is growing recognition of the adverse consequences of gambling, which may comprise vocational disruptions (e.g., job loss; Langham et al, 2015), deviant and criminal behaviour (Roberts, Sharman, King, Bayston, & Bowden-Jones, 2019), as well as severe financial problems (Grant, Schreiber, Odlaug, & Kim, 2010), mental health issues (Krause et al, 2018), and interpersonal difficulties (Roberts et al, 2018). The increasing awareness of the magnitude of these issues has provided impetus for initiatives to reduce maladaptive gambling and associated harms (Public Health England, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing recognition of the adverse consequences of gambling, which may comprise vocational disruptions (e.g., job loss; Langham et al, 2015), deviant and criminal behaviour (Roberts, Sharman, King, Bayston, & Bowden-Jones, 2019), as well as severe financial problems (Grant, Schreiber, Odlaug, & Kim, 2010), mental health issues (Krause et al, 2018), and interpersonal difficulties (Roberts et al, 2018). The increasing awareness of the magnitude of these issues has provided impetus for initiatives to reduce maladaptive gambling and associated harms (Public Health England, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous findings between self-esteem and work addiction, it is hypothesized that self-esteem mediates the relationship between both self-oriented perfectionism and work addiction, and between socially prescribed perfectionism and work addiction. Based on theories of the emotional processes of individuals with work addiction [ 4 , 49 ] and research examining the relationships between other behavioral addictions and rumination [ 57 , 58 ], it is hypothesized that a higher level of maladaptive rumination (i.e., brooding) predicts a higher level of work addiction. According to empirical evidence examining the relationship between low self-esteem and more intensive maladaptive rumination [ 59 , 60 ], it is hypothesized that brooding will mediate the relationship between self-esteem and work addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Based on theories of the emotional processes of individuals with work addiction [ 4 , 49 ] and research examining the relationships between other behavioral addictions and rumination [ 57 , 58 ], it is hypothesized that a higher level of maladaptive rumination (i.e., brooding) predicts a higher level of work addiction.…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of the relationship between gambling severity and depression is not clear in the literature. Previous works point out a co-occurrence between depression and pathological gambling symptoms 78 , 79 , with gamblers with comorbid depression having more severe problems, or with some mood-related sub-aspects, such as rumination, prolonging or intensifying the relationship between depression and problem gambling. A very recent mediational study found that deficits in non-acceptance, goals, strategies, and clarity in emerging adult gamblers, mediated the relationship between problem gambling and depression 80 .…”
Section: Discussionmentioning
confidence: 99%